Complete stories and poems - Poe, Edgar Allan, 1809-1849. (Garden City, N.Y., Doubleday, 1966)
Brings together Poe's stories and poems in one volume.
Wilson's Fiction
Wilson's Fiction, October 2010
Adult
English.
Keywords: Fantastic poetry, American; Horror tales, American; American fiction; American poetry; Short stories